2014
DOI: 10.2298/hemind130306034n
|View full text |Cite
|
Sign up to set email alerts
|

Photostability of piroxicam in the inclusion complex with 2-hydroxypropyl-β-cyclodextrin

Abstract: The aim of this work is the protection of piroxicam from photodegradation by forming inclusion complex with 2-hydroxypropyl-β-cyclodextrin. Piroxicam:2-hydroxypropyl-βcyclodextrin molecular inclusion complex was prepared by coprecipitation method with 1:1 molar ratio. Structural characterization of the complex, the corresponding physical mixture and complexing agents of piroxicam and 2-hydroxypropyl-β-cyclodextrin was carried out by X-ray diffraction (XRD), proton nuclear magnetic resonance (1 H-NMR) and Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…Aromatic ketones moved the molar absorptivity towards higher wavelengths and consequently acted as more photosensitive agents [23]. A recent research showed the improved photostability of the usnic acid and piroxicam in the inclusion complexes with 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) [24,25].…”
mentioning
confidence: 99%
“…Aromatic ketones moved the molar absorptivity towards higher wavelengths and consequently acted as more photosensitive agents [23]. A recent research showed the improved photostability of the usnic acid and piroxicam in the inclusion complexes with 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) [24,25].…”
mentioning
confidence: 99%
“…The X-ray diffractometry studies (Figure 3) confirm the crystalline nature of PX and β-CD, as well as the amorphous state of Me-β-CD and HP-β-CD. PX have a number of sharp peaks at 9.1°, 10.3°, 15.2°, 15.9°, 16.4°, 17.2°, 19.8°, 23.1°, 26.4°, and 27.1° [26]. Some of these peaks are already present in the diffractograms of physical mixtures, but appear of lower intensity compared to those of the pure drug.…”
Section: Resultsmentioning
confidence: 99%
“…PX exhibits characteristic bands at 3330 cm −1 (-NH stretching), 2970 cm −1 (-OH stretching), and 1630 cm −1 (C=O group of the cubic form) [15]. The spectra of CDs present a profile without distinctly high peaks in the range of 3000–3700 cm −1 (–OH groups) and in the range of 2800–3000 cm −1 (C-H groups) [14,26,27]. Physical mixtures shows the presence of both components (PX and CD).…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticosteroids pregna-1,4-dien-3,20-diones [24] betamethasone and its esters [25,26] betamethasone-17 valerate [27] mometasone furoate [28] hydrocortisone 21-acetate [29] prednisolone [30] fluocinolone 16,17-acetonide [31,32] desonide [33,34] Retinoids vitamin A [35] tretinoin [36][37][38][39][40][41][42][43][44] isotretinoin [36,37,45] adapalene [46,47] tazarotene [48] Antifungal drugs clotrimazole [49,50] bifonazole [51] itraconazole [52,53] terbinafine [54] Non-steroidal antiinflammatory drugs piroxicam [55][56][57] naproxen [58][59][60][61] diclofenac [57,58,62] ketoprofen [63][64][65][66] ibuprofen …”
Section: Drug Class Active Pharmaceutical Ingredientmentioning
confidence: 99%
“…The relationship between pH and the degradation rate is U-shaped, with an increase in the degradation rate in acidic and alkaline regions [109]. The inclusion complex of piroxicam with 2-hydroxypropyl-β-cyclodextrin increases the photostability by offering protection from daylight for up to 30 days [56]. Glass et al identified four photodegradation products of piroxicam after irradiation of its methanolic solution: (i) 2-methyl-1,2-benzisothiazol-3(2H)-one1,1-dioxide; (ii) N-(2-pyridyl)-methoxy-formyl-amide as a result of oxygen incorporation into piroxicam; (iii) N-(2-pyridyl)-methoxyamide being a result of decarbonylation of N-(2-pyridyl)-methoxy-formyl-amide; and (iv) N-methyl-N -(2-pyridyl)-ethane-diamide formed as a consequence of cleavage of the sulfur-nitrogen bond in the carboxylic acid.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%